2016
DOI: 10.1016/j.cell.2016.05.075
|View full text |Cite
|
Sign up to set email alerts
|

A Long Noncoding RNA lincRNA-EPS Acts as a Transcriptional Brake to Restrain Inflammation

Abstract: SUMMARY Long intergenic noncoding RNAs (lincRNA) are important regulators of gene expression. Although lincRNAs are expressed in immune cells, their functions in immunity are largely unexplored. Here we identify an immunoregulatory lincRNA, lincRNA-EPS, that is precisely regulated in macrophages to control the expression of immune response genes (IRGs). Transcriptome analysis of macrophages from lincRNA-EPS-deficient mice, combined with gain-of-function and rescue experiments, revealed a specific role for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
360
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(373 citation statements)
references
References 33 publications
5
360
2
Order By: Relevance
“…LncRNAs may control many aspects of innate immunity such as regulation of inflammatory mediators, differentiation, and cell migration through their interaction with various RNA-binding proteins (16,47,48). Most studies demonstrate that lncRNAs regulate inflammatory genes via transcription mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs may control many aspects of innate immunity such as regulation of inflammatory mediators, differentiation, and cell migration through their interaction with various RNA-binding proteins (16,47,48). Most studies demonstrate that lncRNAs regulate inflammatory genes via transcription mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…NF-kB signaling can regulate both the activation and inhibition of lncRNA expression (46,47). It was first described in 2013 in mouse bone marrow-derived dendritic cells that transcription of lncRNA genes in response to TLR signaling is activated in an NF-kB-dependent manner (26).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest this region also has a role in mature Tregs, balanced with AR5. lncRNAs commonly operate within ribonucleoprotein complexes with specific TFs (36), chromatin modifiers (28), or Hnrnp proteins (37,60), and we propose that Flicr may target a repressive complex to the CNS3/AR5 region of Foxp3.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the wide application of the two generation sequencing technology, the mysterious veil of lncRNA was gradually uncovered, the accumulated research data show that lncRNA is involved in the regulation of cell differentiation and ontogeny and other important life processes in many aspects such as: lncRNA participates in the process of X chromosome silencing [6], chromosome modified [7], genome modified [8], transcriptional activation [9], transcriptional interference [10], and nuclear transport [11], etc. LncRNA is also closely related to major human diseases [12][13][14][15]. Examples include: (1) in some cases, the overexpression of lncRNA is associated with certain cancers, including breast cancer, prostate cancer and leukemia et al [12][13][14]; (2) lncRNA also plays an important role in the immune system [15], for instance the research team led by Katherine A. Fitzgerald of the University of Massachusetts medical school confirmed that a lncRNA (lincRNA-EPS) can play a transcriptional brakes and play a role in restricting inflammation.…”
Section: Modeling and Analysis Of Lncrnamentioning
confidence: 99%